Colorimetric loop-mediated isothermal amplification assay for detection and ecological monitoring of Sarocladium oryzae, an important seed-borne pathogen of rice - Choudhary, Prassan; Goswami, Sanjay Kumar; Chakdar, Hillol; Verma, Shaloo; Thapa, Shobit; Srivastava, Alok Kumar; Saxena, Anil Kumar (Frontiers in Plant Science, 2022)
Accurate and timely disease detection plays a critical role in achieving sustainable crop protection. Globally, rice has been a staple crop for centuries plagued by the diseases that greatly hamper its productivity. Sheath rot, an emerging disease of rice caused by the seed-borne pathogen Sarocladium oryzae, has reportedly caused heavy losses to agricultural produce in recent years. Our study has led to the development and validation of a LAMP assay for early detection of S. oryzae, the causal agent of sheath rot from the live-infected tissues, seeds, weeds, and environmental samples. The assay could detect as low as 1.6 fg/μl of the pathogen in 15 min. The assay was implemented to bio-surveil the presence of this pathogen by testing it on three weed species (Echinochloa colona, Echinochloa crus-galli, and Cyperus teneriffae) growing around the rice fields. The results showed the presence of the pathogen in two of the weed species viz. E. colona and E. crus-galli. The assay was used to test 13 different rice varieties for the presence of S. oryzae in seeds. In total, three of the varieties did not show the presence of S. oryzae in their seeds while the rest were found to harbor the pathogen. The developed assay can effectively be used to detect and screen the presence of S. oryzae in live samples including seeds and field soil.